Capacity Fading Model of Vanadium Redox Flow Battery Considering Water Molecules Migration. Issue 15 (8th December 2022) - Xiong, Rui; Xiong, Binyu; Zhang, Qingyong; Shi, Shaoyue; Su, Yixin; Zhang, Danhong
ABSTRACT: During the long-term operation of a vanadium redox flow battery (VRB), the battery is subject to capacity fading as vanadium ions diffuse at different rates. Water molecules will migrate from one side to another resulting in an imbalance of electrolyte volume. An accurate model is needed to describe the capacity fading process. In existing models, a capacity fading factor due to vanadium ions crossover is well addressed, but the fading factor due to water molecule migration is often ignored. In this paper, a capacity fading model considering the migration of water molecule migration of VRB based on conservation of mass and charge is proposed. Based on this model, the electrolyte volume variation and capacity fading can be observed. Meanwhile, the mechanism of battery capacity fading can be analyzed from the imbalance of reactant concentrations. From the comparative simulation results, the influence of the migration of water molecules on capacity fading is explored. Simulation results show that the proposed model and in-depth analysis provide a cost-effective way to describe the mechanism of VRB capacity fading.